The youth of today and the sports of tomorrow - Kogan O.S.; Yamileva R.M.; Greb A.V.; Bresler M.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the characteristics of student sports engagement with innovative computer technologies in sports, particularly the prevalence of esports games among students. Methods and structure of the study. The research into the prevalence of esports and digital sports among young people is based on the findings of scholarly publications. To gauge the preferences of students at Ufa State Petroleum Technical University (USPTU), a survey was conducted, which included a questionnaire on their choice of these sports. Results and conclusions. Our investigation, which draws upon the scientific literature and the perspectives of USPTU students, reveals a growing trend among young people towards computer games and competitions in digital disciplines that utilize advancements in game development, esports, robotics, augmented and virtual reality, information technology, and artificial intelligence.